Rating tendencies of the innovative development prognostication system at the industrial enterprise - A.S. Rosokhata (Marketing i Menedžment Innovacij, 2014)
The aim of the article. The article deals with the formational process of enterprise innovative directions on the basis of nowadays modern tendencies structured analysis. The practical realization of the innovative development prognostication process at the enterprise is confined mostly to the current market condition and economic viability analysis. The system of development innovative directions prognostication has no systematic complex approach, structured organization, set of elements, which provide to collect and rate nowadays tendencies, i.e. perspectives for future development. The object of an article is to form approach to the modern tendencies rating, which are observed within the introduction system concerning innovative development perspective directions prognostication at the enterprise – trend-watching. The results of the analysis. The article demonstrates the research on concepts “trend” and “tendencies” economic aspect definition. The author presents the approach to prognosticate innovative development directions of industrial enterprises, based on social and economic development urgent tendencies research; that is the main point to investigate the research direction – trend-watching. The methodic of tendencies rating to decrease subjectivity level while prognosticating enterprise development directions, which is based on tendencies spreading speed determination, is also suggested. The main essence of the tendencies development quantitative concept consists in the fact, that, in order to know which level will be achieved in this or that process, it is necessary to know average speed of its change. So, the average speed of the process change may be rated. The article presents three tendencies features, including time, place and action. These perceptions give reason to define the tendency speed, that is the resultant factor of tendency development and spreading factor in the proper time taking into account the geographical space. In order to determine farness of the tendency spreading in various geographical space zones author investigates that tendency belongs to the studied object. The experience to conduct marketing research, including geographical segmentation of interaction subjects at the industrial enterprise, is the main point to allocate tendencies spreading. There are distinguished such geographical space zones of the tendency spreading as enterprise productive branch; enterprise region; country where enterprise is working; world space in general. Conclusions and directions of further researches. Each geographical space zone is given farness coefficient; it results in making the formula to calculate tendencies spreading intensity, which is the base to express mathematically the speed of tendency spreading. To calculate the speed of tendency spreading will increase the objectivity to make decisions and allow to form a range of investigated tendencies in quantitative concept. Quantitative data concerning tendencies spreading speed gives opportunity to take up qualitative analysis into the new level, decreasing the subjectivity level and using formalized methods of innovative development directions prognostications at the industrial enterprises. The perspectives for further research consist in forming of approach to group tendencies by the spreading speed factor with aim to define base to create innovative development directions, i.e. the key aspects, characterizing investigated processes and phenomena.